Východoevropsk á tematika v díle Jáchyma Topola - Říha, Ivo (Slavia Occidentalis, 2011)
The study focuses on the characteristic features of Jáchym Topol´s creative style as represented in his prosaic work of the recent decade. Special attention is paid to the artistic reflexion on the history of Central and Eastern Europe in the context of poetics of literary characters.